Limiting the Formation of Carbon Monoxide in the Formox-Process - Okutan,Rezan (2024)
In the Formox-process, methanol is converted to formaldehyde via partial oxidation on a heterogeneous iron-molybdate catalyst. To an extent, the formed formaldehyde (FA) is over-oxidized into carbon monoxide (CO) which cannot be recycled into FA. As CO affects the environment negatively and decreases the process economy, internal attempts have previously been made to decrease the CO formation of the process. This project has been conducted with the intent to decrease the CO formation of the process by at least 0.5 percentage points from today’s roughly 4.5%. In this project, CO reduction of the Formox-process has been attempted by investigating two different pathways; with the first being addition of a readily combustible material known as a Pore Former in various amounts to increase the porosity of the catalyst, as well as doping the catalyst with a metal oxide to act as a hardener. Changes to the mixing method of these ingredients has also been investigated. Analysis of the produced catalyst pellets showed that after these changes, the catalyst is either too fragile to be tested at a pilot scale, or exhibit too low porosity to be deemed promising for further study. The other method that was tested involved replicating a washing step of the catalyst that is currently done in large-scale production. A washing liquid with a lower number of ions compared to the one being currently used was tested and compared to commercial references. Three samples with different washing liquids were produced and tested at a pilot scale, and the sample washed with process water showed an increased FA yield and a decreased byproduct yield compared to the commercial reference. However, the samples also exhibited an increased CO yield. These results potentially indicate a shift in the nature of the active sites of the catalyst from acidic to basic, but further testing must be done to determine the exact nature of the changes that have been made. Overall, the results provide a good basis for further study.
Keywords: Heterogeneous Catalysis; Chemical Engineering; Formaldehyde